2020
DOI: 10.1002/ange.202001452
|View full text |Cite
|
Sign up to set email alerts
|

Complete Charge Regulation by a Redox Enzyme Upon Single Electron Transfer

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…61 In general, charge regulation might be an evolutionarily adopted property by which proteins maintain Z during ligand binding 62 or catalysis. 63 For example, we have already shown that superoxide dismutase maintains tight regulation of its Z during single electron transfer (and fluctuations in pH). We hypothesize that this property is significant to SOD1's ability to bind superoxide independent of its copper oxidation state at various subcellular pH values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…61 In general, charge regulation might be an evolutionarily adopted property by which proteins maintain Z during ligand binding 62 or catalysis. 63 For example, we have already shown that superoxide dismutase maintains tight regulation of its Z during single electron transfer (and fluctuations in pH). We hypothesize that this property is significant to SOD1's ability to bind superoxide independent of its copper oxidation state at various subcellular pH values.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that this property is significant to SOD1's ability to bind superoxide independent of its copper oxidation state at various subcellular pH values. 63,64 Examining charge regulation during crowding of proteins that do or do not regulate their charge upon ΔpH or ET is an area of interest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations